Mental health trajectories in undergraduate students over the first year of university: a longitudinal cohort study - Kate E Saunders; Kiera Louise Adams; Charles Donald George Keown-Stoneman; Anne C Duffy (BMJ Open)
Objective This study examined the association between candidate psychosocial and lifestyle variables and the trajectories of clinically significant anxiety and depressive symptoms from entry to completion of first-year university.Design A longitudinal cohort studyParticipants First-year undergraduate studentsMethods We analysed the responses of 1686 first-year undergraduate students attending Queen’s University who completed electronic surveys at both the beginning and completion of their academic year. Predictors of change in positive anxiety and depressive symptom screens (based on exceeding validated symptom threshold scores) were identified using logistic regression.Results Increased university connectedness reduced the odds of emergent significant depressive and anxiety symptoms in healthy students and increased the odds of recovery in students who screened positive at the start of university. Students who screened positive for depression or anxiety at university entry were less likely to recover if they had a lifetime history of internalising disorders. Healthy students who increased their drug use over their first year had higher odds of developing significant levels of both anxiety and depressive symptoms by completion of the academic year.Conclusions Moderate to severe levels of anxiety and depressive symptoms are common among students at entry to university and persist over the first year. University connectedness may mitigate the risk of persistent or emergent symptoms, whereas drug use appears to increase these risks. Findings have implications for university well-being initiatives.